(untitled) (Biological Sciences - PJSIR, 1994)
The influence of complexing agents on bio-ethanol production from molasses has been investigated. The agents are nitrilotriacetic acid (NTA) and 8 -hydroxyquinoline. They were introduced during the inoculation, propagation and fermentation stages.The increase was between 0.5-1.0% v/v ethanol for NTA and 2.9-3.8% vlv ethanol for 8- hydroxyquinoline.These results as well as the mode of action of the agents were discussed.